Unveiling the physiological and molecular basis of Mycobacterium tuberculosis complex biofilms: the potential role of Rv2488c - Baeta, Tiago Filipe Serras (2016)
Tese de mestrado, Biologia Molecular e Genética, Universidade de Lisboa, Faculdade de Ciências, 2016